Membangun Karakter, Kreativitas dan Inovasi Mahasiswa melalui Expo Kewirausahaan - Widiawati, Wilda; Rusdin, Rista Astari; Suharman, Suharman; Haliq, Muh Idham; Elihami, Elihami (MASPUL JOURNAL OF COMMUNITY EMPOWERMENT, 2024)
The Entrepreneurship Expo is an activity designed to buid entrepreneurial character, increase student creativity and innovation. This activity provides students with the opportunity to showcase their products and creative ideas, build networks with entrepreneurs and get feedback and awards. The Entrepreneurhip Expo has several benefits, including building an entrepreneurial character who dares to take risks, never gives up and has a leadership spirit. Increase creativity and innovation by thinking creatively and being innovative in creating new products and ideas. Provides opportunities to present products and ideas and increase competitiveness. The method of implementing the Entrepreneurship Expo includes planning, implementation and evaluation. Planning includes forming a committee, determining themes and objectives as well as carrying out promotion and publications. Implementation includes exhibition stands, seminars and award giving. Evalution includes identifying weaknesses and strengths as well as formulating recommendations for improvement. The results and achievements show an increase in student interest in entrepreneurship, the growth of an entrepreneurial spirit, increased creativity and innovation, the creation of innovative products, the establishment of networks and increased competitiveness. The Entrepreneurship Expo can help students to become future leaders who are able to answers various global challenges.